CHARACTERISTICS OF TEACHER'S QUESTIONS OF AN ELEMENTARY SCHOOL ENGLISH TEACHER AT THE FIFTH YEAR OF SDN GENENG DUWUR 2GEMOLONG KABUPATEN SRAGEN - MAYASARI, HENI AGUSTINA (2007)
This research paper is conducted to give a description of the characteristics of teacher's question. It is aimed at knowing: (1) the characteristics of language used by the teacher in asking questions, and (2) the types of questions that are used by the teacher in teaching learning process. In this research, the writer employed a descriptive qualitative method. The data were derived from all the teacher's questions. The subject of this research is the English teachers at the fifth year of SDN Geneng Duwur 2 Gemolong Sragen and the object of the research is the teacher's question of the fifth year elementary school. After collecting the data, the writer classified them based on the Indonesian questions and the English questions. Then the writer also categorized the teacher's questions into three major types, namely: task, task supervision, and routine question. The result of the research show that during the English class the English teacher uses Indonesian more than English in asking questions (f= 33 or 75%). Then the task question used dominantly by the English teacher during the English class(f=27 or 61,36%). The second place is occupied by task supervision questions (f=14 or 31,82%). Meanwhile, the last rank is routine question (f= 3 or 6,82%). The implication of its research to SDN Geneng Duwur 2 Gemolong, especially to English teachers is when giving questions in teaching learning process, the teacher gives more variation of questions and both of English and Indonesian Questions can be used. Therefore, the students can understand the English questions and their meaning where it can improve the students in English subject.